Influence of layering pattern of modified kenaf fiber on thermomechanical properties of epoxy composites. Issue 1 (February 2020) - Mohammed, AR; Atiqah, MS Nurul; Gopakumar, Deepu A; Fazita, MR; Rizal, Samsul; Hermawan, D; Thomas, Sabu; Khalil, HPS Abdul
Natural fiber-reinforced composites gained considerable interest in the scientific community due to their eco-friendly nature, cost-effective, and excellent mechanical properties. Here, we reported a chemical modification of kenaf fiber using propionic anhydride to enhance the compatibility with the epoxy matrix. The incorporation of the modified woven and nonwoven kenaf fibers into the epoxy matrix resulted in the improvement of the thermal and mechanical properties of the composite. The thermal stability of the epoxy composites was enhanced from 403°C to 677°C by incorporating modified woven kenaf fibers into the epoxy matrix. The modified and unmodified woven kenaf fiber-reinforced epoxy composites had a tensile strength of 64.11 and 58.82 MPa, respectively. The modified woven composites had highest flexural strength, which was 89.4 MPa, whereas, for unmodified composites, it was 86.8 MPa. The modified woven fiber-reinforced epoxy composites showed the highest value of flexural modulus, which was 6.0 GPa compared to unmodified woven composites (5.51 GPa). The impact strength of the epoxy composites was enhanced to 9.43 kJ m −2 by the incarnation of modified woven kenaf fibers into epoxy matrix. This study will be an effective platform to design the chemical modification strategy on natural fibers for enhancing the compatibility toward the hydrophobic polymer matrices.